CRM CAPABILITIES DITINJAU DARI ORIENTASI PELANGGAN, CUSTOMER-CENTRIC ORGANIZATIONAL SYSTEM, CRM TECHNOLOGY TERHADAP SERTA DAMPAKNYA TERHADAP KEPUASAN DAN LOYALITAS - Alam Winulang; Burhanudin Burhanudin (Universitas Islam Lamongan, 2022)
The purpose of this research is to analyze Customer Orientation, Customer-Centric Organizational System, CRM Technology to CRM Capabilities and Their Impact on Customer Satisfaction and Loyalty of PT Asuransi Jasa Indonesia. The population used is the customers of PT Asuransi Jasa Indonesia and the sampling technique is carried out using a purposive sampling technique as many as 130 respondents. This research is a correlation type using a quantitative method approach. The results showed that Customer Orientation had no significant effect on the CRM Capabilities variable, Customer-Centric Organizational System had a significant effect on the CRM Capabilities variable, CRM Technology had a significant effect on the CRM Capabilities variable, CRM Capabilities had no significant effect on Customer Satisfaction,